Effective downlink resource management for wimax networks - Shareef, Zayd Ashraf Najeeb (2018)
The interest in Quality of Service (QoS) for broadband wireless access networks has been growing considerably because of the need for efficient data access, particularly in WiMAX networks. Unlike wireless LANs, WiMAX networks incorporate several QoS mechanisms to guarantee services for Internet applications, such as HTTP, FTP, VoD, and VoIP. These types of applications require additional performance criteria from the underlying network, such as reliability, timeliness, and guaranteed delivery, as well as different levels of service quality. However, in WiMAX downlink communication, such criteria are not sufficiently offered. This has led to QoS degradation, which burdens the ISPs. Furthermore, the existing resource management in WiMAX downlink communication lack the supporting effective scheduling, bandwidth allocation, and packet transmission as in one framework. Hence, a comprehensive framework that fulfils the QoS constraints in downlink communication has become more significant for all types of Internet applications. Herein, we propose a downlink communication framework called Effective Downlink Resource Management (EDRM) in WiMAX Internet infrastructure networks. It aims to achieve QoS assurances and high network performance for better user experiences. Our EDRM framework involves three functions: Class-Based Scheduling (CBS) algorithm, Dynamic Bandwidth Allocation (DBA) scheme and Link Session Management (LSM) policy. Each of these three functions contains various modules to deal with several services such as data traffic, bandwidth resources, and packet delivery, respectively. We implemented the EDRM framework in a simulated environment, using OPNET Modeler. In terms of jitter, we succeeded in recording 41% improvement in VoD, 45% enhancement of average delay for FTP, and 21% for HTTP in CBS among the other existing algorithms. Meanwhile, in DBA, we recorded 15% of improvement in terms of network throughput and bandwidth utilisation, as compared to the other scheme. Finally, in LSM, we achieved 24% of improvement in packet delivery ratio and immense packet loss reduction as compared to the other competitive policy. Therefore, EDRM maximised the data transfer rate and reached effective transmission and utilisation in all the developed functions. Optimistically, the comprehensive resource management for downlink communication in WiMAX such as EDRM can have notable advantages and achieve substantial performance that lead to improved user satisfaction.